2009
DOI: 10.1227/01.neu.0000337127.73667.80
|View full text |Cite
|
Sign up to set email alerts
|

Results, Outcomes, and Follow-Up of Remnants in the Treatment of Ophthalmic Aneurysms

Abstract: Despite the difficulties presented by ophthalmic aneurysms, these lesions can be successfully managed by a multidisciplinary team. Imaging follow-up of patients is important, as there is a risk of aneurysm regrowth after either coiling or clipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Visual deficits associated with clipping surgery for paraclinoid carotid artery aneurysm can be caused by vascular compromise, manipulation of the optic nerve, thermogenic effects from high-speed drilling of the clinoid process, or other unknown causes. 3,5,6,10,19,20 For the patient in Case 2, surgical manipulation was the most likely cause of the postoperative visual worsening because VEPs were attenuated during the suction decompression procedure.…”
Section: Paraclinoid Carotid Artery Aneurysm and Visual Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual deficits associated with clipping surgery for paraclinoid carotid artery aneurysm can be caused by vascular compromise, manipulation of the optic nerve, thermogenic effects from high-speed drilling of the clinoid process, or other unknown causes. 3,5,6,10,19,20 For the patient in Case 2, surgical manipulation was the most likely cause of the postoperative visual worsening because VEPs were attenuated during the suction decompression procedure.…”
Section: Paraclinoid Carotid Artery Aneurysm and Visual Functionmentioning
confidence: 99%
“…Of these 6 patients, visual field defects occurred in 2 patients, visual acuity diminution in 1, and transient palsies of the sixth cranial nerve in 3. In 2009, Fulkerson et al 6 reported that new visual loss occurred in 6 (4.8%) of 126 ophthalmic aneurysm patients who underwent craniotomy. In contrast, Barami et al reported that vision impairment associated with clipping for paraclinoid carotid artery aneurysms might comprise up to 20% of cases at 6-month follow-up examination.…”
Section: Paraclinoid Carotid Artery Aneurysm and Visual Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of pretreatment visual symptoms has been reported to occur in 23%-32% of patients with ICA aneurysms in previously reported studies, a rate comparable to the 29% of patients with visual complaints at initial presentation in the current series. 2,4,5 Resolution of visual symptoms caused by intracranial aneurysms following treatment has been reported to be more successful in instances in which the target aneurysm was treated within 3 months of visual symptom onset. 2 The literature also provides evidence that microsurgery is superior to embolization with regard to resolution of visual symptoms, with one study reporting improvement or resolution of visual symptoms in 75% of aneurysms treated with microsurgery versus 38% of patients treated with embolization.…”
Section: Discussionmentioning
confidence: 99%
“…18 This finding may be explained by the ability of microsurgery to decompress the aneurysm through a postclipping aneurysm puncture and decompression of the aneurysm, which relieves the mass effect of the aneurysm on the anterior visual pathways. 3,12,21 Fulkerson et al 5 studied the treatment of 134 patients, 97 of whom harbored unruptured aneurysms, and observed an incidence of pretreatment ophthalmological findings in 27.8% of unruptured aneurysms. New visual deficits were observed in 4.8% of patients undergoing craniotomy for microsurgical clipping without worsening visual deficits in the 26 patients undergoing coil embolization.…”
Section: Discussionmentioning
confidence: 99%